Elements of music that work to improve sleep, a narrative review - Pan, Ethan Y.; Wang, Wei (Frontiers in Sleep, 2025)
Sleep health is essential for overall wellbeing; however, millions of people worldwide experience poor sleep quality due to insomnia, stress, or lifestyle-related disturbances. Pharmacological and behavioral treatments, while effective, remain limited by side effects, accessibility barriers, or patient adherence. In contrast, music is an accessible, low-cost, and non-invasive intervention that is increasingly used by individuals to improve sleep. This narrative review synthesizes findings from randomized controlled trials and meta-analyses to identify the musical elements and delivery methods that are most effective in enhancing sleep quality. Across studies, listening to music consistently reduced sleep-onset latency, improved sleep efficiency, and increased total sleep time. Music that was slow in tempo (60–80 bpm), soft and smooth in melodies, instrumental, and simple in structure, often classical or new age, was most effective. Cultural familiarity, nature sounds, and religious music also demonstrated benefits in specific contexts. Innovative approaches, such as brain-wave music and binaural beats, show promise but require further validation. Optimal dosing included 30–45 min of daily listening before bedtime at comfortable volume levels. Despite strong evidence of short-term benefits, gaps remain in our understanding of the long-term effects, mechanisms of action, and impacts on youth populations. Future research should explore how personalized music interventions and artificial intelligence-generated compositions may advance sleep health. Overall, this review highlights the elements at work that make music a safe, scalable, and culturally adaptable adjunct to traditional sleep therapies.